Performance improvement of DVR using a new numerical LPF based on VFF-RLS and fuzzy logic controller. (September 2018) - Fallah, M; Kazemzadeh, R; Madadi Kojabadi, H
This paper deals with improving the technique of a dynamic voltage restore (DVR). The DVR is a dynamic solution to protect sensitive loads against voltage sags and swells. The DVR can be implemented to protect a group of medium- or low-voltage consumers. Various control methods are proposed to the DVR control, such as pre-sag, in-phase, and minimum energy compensation algorithms, etc. This study presents a modification of the pre-sag method of DVR control in which the steady state and transient response of the pre-sag method are improved. For this purpose, a numerical low pass filter (NLPF) based on a fuzzy logic controller (FLC) and recursive least squares with variable forgetting factor is proposed. The suggested NLPF is replaced instead of the conventional LPF in the pre-sag method structure of the DVR control. With this substitution the steady state and transient response of the DVR are improved. Simulation and experimental results verify the validity and good performance of the proposed method.